Sex-specific relationships between sprint swim performance and tethered swimming in high-performance swimmers - Keating, R.; Kennedy, R.; McCabe, C. (Sports Biomechanics, 2025)
This study investigated the relationship between sprint swim performance and outputs derived from fully-tethered and semi-tethered swimming assessments in high-performance male and female swimmers. Twenty elite/highly trained swimmers (9 females, 11 males), specialising in 50-100 m events, completed all assessments in a randomised order in a 25 m pool. 50 m time-trial variables included total time, stroke rate, stroke length and swim velocity. A fully-tethered protocol involved 20 s of maximal swimming to determine peak and mean force, impulse and stroke rate. A semi-tethered protocol required swimmers sprinting 10 m with incremental loads (1, 3, 5 kg for females; 1, 5, 9 kg for males). Load-velocity and force-velocity profiling derived theoretical maximum velocity (V0), theoretical maximal load/force (L0/F0), relative to body mass (rL0/rF0) and absolute and relative slope between the two variables. All semi-tethered variables except slopes showed large to extremely large correlations with 50 m total time (r = -0.618 to -0.955, p < 0.05) in males and females. In contrast, fully-tethered variables showed heterogeneous correlations, suggesting stroke- and sex-specific analyses may be more appropriate. These findings highlight semi-tethered profiling as an effective and ecologically valid tool for assessing sprint performance in high-performance swimmers and informing targeted training interventions.